2021
DOI: 10.1021/acs.jafc.1c05141
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Magnesium Deficiency on the Quality Constituents of Hydroponic-Cultivated Tea (Camellia sinensis L.) Leaves

Abstract: Magnesium (Mg) plays important roles in photosynthesis, sucrose partitioning, and biomass allocation in plants. However, the specific mechanisms of tea plant response to Mg deficiency remain unclear. In this study, we investigated the effects of Mg deficiency on the quality constituents of tea leaves. Our results showed that the short-term (7 days) Mg deficiency partially elevated the concentrations of polyphenols, free amino acids, and caffeine but decreased the contents of chlorophyll and Mg. However, long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…In our study, we observed an increase in chlorophyll content that positively correlated with Mg concentration, while acid stress led to a decrease. Notably, Mg deficiency generated a significant reduction in chlorophyll content within 30 days, indicating that the two are tightly linked, as previously reported [29]. In agricultural practice, reduced chlorophyll content results in interveinal chlorosis in mature plant leaves [36], although our experimental plants displayed no significant chlorosis at any time.…”
Section: Chlorophyll and Root Vitality In Tea Seedlingssupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, we observed an increase in chlorophyll content that positively correlated with Mg concentration, while acid stress led to a decrease. Notably, Mg deficiency generated a significant reduction in chlorophyll content within 30 days, indicating that the two are tightly linked, as previously reported [29]. In agricultural practice, reduced chlorophyll content results in interveinal chlorosis in mature plant leaves [36], although our experimental plants displayed no significant chlorosis at any time.…”
Section: Chlorophyll and Root Vitality In Tea Seedlingssupporting
confidence: 83%
“…The concentration of chlorophyll in fresh mature leaves was determined using a modified version previously described [29]. In brief, the leaves were washed and dried and primary veins were removed, followed by chopping into small pieces and placement (0.20 g) in a 25 mL volumetric flask.…”
Section: Determination Of Chlorophyll Concentration and Root Viabilitymentioning
confidence: 99%
“…Additionally, the variations in the content of the identified antioxidant compounds were explained by the variations in exchangeable magnesium, cation exchangeable capacity, annual precipitation (BIO12), pH, annual mean temperature, precipitation, annual mean temperature (BIO01), clay, bulk density, and topographic wetness index (TWI) based on analysis of variance (ANOVA), as shown in Table 3 . Magnesium deficiency in plants can cause a decrease in total phenolic content [ 36 ], and exchangeable magnesium is crucial for generating the main phenolic compounds responsible for the antioxidant activity of C. indicum . From this result, cation exchange capacity, which shows the ability of soil to hold and supply nutrients such as magnesium and calcium, is also an important parameter for plant growth, as mentioned in previous studies [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…(2022) demonstrated a positive correlation between Mg 2+ content and sugar accumulation in navel oranges, substantiating the role of Mg 2+ in sugar synthesis. Furthermore, Li et al. (2021) investigated Camellia sinensis and revealed that adequate Mg 2+ levels enhance the production of volatile compounds, thus improving the quality constituents of Hydroponic-Cultivated Tea.…”
Section: Impact Of Magnesium On Crop Developmentmentioning
confidence: 99%